Inferior alveolar nerve block using internal oblique ridge as landmark - K Thangavelu; S Sabitha; R Kannan; K Saravanan (Wolters Kluwer Medknow Publications, 2012)
Background: Inferior alveolar nerve [IAN] Block is the most commonly used technique to anesthetize the mandibular teeth, gingival tissues, and mucosa anterior to mental foramen. Several failures are observed in the current techniques due to technical difficulties and non reliable landmarks. A simple technique with higher success rate is essential and fundamental. Aims and objective: The objective of this study was to find an Inferior Alveolar Nerve block with easier technique and simple reliable landmark, which has higher success rate.. Material and methods: This study was based on the experience gained from 400 patients, 200 male and 200 female, age 30 to 60 years, scheduled for lower teeth extractions and who have given their informed consent to participate. Results: In 382 patients the symptoms of inferior alveolar nerve anesthesia developed in 1st nerve block. The technique proved to be effective in 95% of the cases. Conclusion: The Inferior Dental nerve anesthetic technique using internal oblique ridge as main landmark is an appropriate alternative option to anesthetize inferior alveolar nerve.